Designing a child-centred, quantitative measure of inter-ethnic relations : a mixed methods approach - Babineau, Kate Alexis (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2014)
The main objective of the current body of research was to design and validate a broad and coherent, child-centred quantitative measure of inter-ethnic relations. Specifically, it sought to construct a measure that addressed certain fundamental gaps in the existing child-based, quantitative inter-ethnic instruments. First, it aimed to build a measure that was thoroughly child-centred in its formulation, its content, and its presentation. Next, it strived to make the measure both broad and coherent, capturing aspects of children’s inter-ethnic relations from various layers of their ecological environment. Acknowledging the need for strong and t ransparent psychometric qualities, a highly detailed evaluation of the measure's reliability and validity was conducted. Often, these critical components of quantitative research are brushed over when in fact, they are fundamental to the legitimacy of any quantitative study, particularly when conducting child-based research. This project relied upon non-parametric item response theory scaling analyses to assess the reliability and sensitivity of the current measure. A battery of robust validation techniques was built into the design of the project, ensuring a multilevel evaluation of the new measure’s ability to accurately capture real world phenomena. Finally, the project aimed to design a measure that is valid for use with children in new migrant communities, an area that is highly relevant in the current international climate but generally under-represented in existing, child-based quantitative inter-ethnic relations research. The measure was then assessed in an area of demonstrated need: the association between inter-ethnic relations and mental health. A worthy objective in its own right, this also served to further build construct validity of the new measure.
Keywords: Social Work and Social Policy, Ph.D.; Ph.D. Trinity College Dublin